Usefulness of Psychiatric Intervention in a Joint Consultation for the Treatment of Burning Mouth Syndrome: A Monocentric Retrospective Study - Vinciane Le Bris; Myriam Chastaing; Martine Schollhammer; Emilie Brenaut; Laurent Misery (Medical Journals Sweden, 2019)
Primary burning mouth syndrome is a term used for chronic oral mucosal pain with no identifiable organic cause. The aim of the study was to evaluate the usefulness of a psychiatric intervention for treating burning mouth syndrome based on a joint consultation with a psychiatrist and a dermatologist. The study was proposed to all patients who visited this consultation group between 2001 and 2017 for the treatment of primary burning mouth syndrome. The patients answered a questionnaire that was administered via mail. Of the 57 patients diagnosed with primary burning mouth syndrome, 38 were included. Seven patients (18.4%) no longer had pain; 8 (21.1%) estimated that the pain had decreased by greater than 50%; 11 (28.9%) estimated the decrease at between 30 and 50%, and 12 (31.6%) estimated a less than 30% decrease. Only 14 patients (36.8%) remained under treatment with antidepressants, as compared to 63.2% before the psychiatric intervention. This psychiatric intervention could be considered a valuable tool in the global burning mouth syndrome treatment strategy.